Three-dimensional foot scanning system with a rotational laser-based measuring head - Novak, Boštjan (Strojniški vestnik, 2014)
Three-dimensional (3D) measurements of the feet is crucial for the correct design and selection of shoes. Badly-fitting shoes are one of the major causes of pain, foot related diseases and injuries of the feet. This article presents a new system for 3D foot-shape measurements which is based on the laser-multiple-line-triangulation principle. The main part of a system is the measuring head comprising a three laser lines projection unit and two cameras, which rotate around the centre of the platform that the customer stands on, and measures both feet simultaneously. The developed software analyzes the different foot dimensions and suggests the most suitable model and size of a shoe from a database to the customer. Validation experiments have been presented to demonstrate the measuring precision of the system. The results show that the standard deviation for all feet dimensions is better than 0.6mm in case of test objects.
Keywords: 3D meritve stopal; dimenzije stopala; prileganje obutve; večlinijska laserska triangulacija